Physical activity in commuting, household, leisure-time, or work: which domain is associated with lower stress in adult workers? - Santos, Marina (2016)
The aim of the study was to investigate the association of the physical activity domains and types of physical activity practiced during leisure time with the occurrence of stress in workers. This is a cross-sectional survey, conducted from 2006 to 2008, with a representative sample of industrial workers (n = 47, 477; 69% men). Data were collected via questionnaire. For statistical analysis, a Poisson regression with adjustment for robust variance was used in Stata 13.0. Women who were physically active during leisure time (19.9%; IC95%: 19.0−20.7) had lower occurrences of stress than those who were physically inactive in this domain (14.2%; IC95%: 13.3−15.2). Among men, those active at home (11.6; IC95%:11.1−12.0 vs. 12.9%; IC95%:12.4−13.5), during leisure time (10.2%; IC95%: 9.8−10.6 vs. 15.1%; IC95%: 14.4−15.7), and at work (11.7%; IC95%: 11.3−12.1 vs. 13.3%; IC95%: 12.6−14.0) had lower occurrences of stress than their peers. As the number of domains that contained physical activity increased, stress occurrence tended to decrease for both sexes. The types of leisure time physical activities associated with a lower occurrence of stress in women were sports (11.1%), gymnastics/weight lifting (13.2%), and dance (14.5%); similar results were observed for men who engaged in jogging (9.0%), sports (9.7%), and walking (10.1%). Physical activity in the leisure time domain, for women and men workers, including sports practice among women and jogging among men, were associated with lower stress occurrences.